Improvement of Training Programme during COVID19 Pandemic on Private Institution - Khoo , Huah Kok (ASEAN Journal of Open and Distance Learning, 2022)
The COVID-19 epidemic has caused many organizations to experience substantial makeover, reconsidering crucial feature of their business development and use of know-how to maintain processes at the same time as following to an altering setting of strategics and difference procedures. The purpose of this paper is to provide the introduction on the impact of the job of the school principal during the Covid-19 pandemic and the problem affected by the epidemic in education. The exertion of managing the occurrence from spreading further has made world frontrunners improve splendid-strict procedures to break the chain of COVID-19. The World Health Organization (WHO) (2019) has suggested having social distancing and bodily distancing, but it has generated tough choices for every nation to implement. In March 2020 Malaysia had adopted “large-scale social constraints” because of the escalating number of people infected with COVID-19. As a result, working from home and home-schooling for students ranging from the primary childhood education level to higher schooling were practiced. There is an urgent need of a good training program due to the unexpected consequence of the epidemic in school. The novice principals without much experience in handling and managing the condition have deteriorated the situation. Hence there is an immediate need for the application of the training program. Regardless of the inception of Covid-19 and its associated challenges, all program leaders must stay on enrolled and participated in the training program. (Abstract by author)